Bimerons as Edge States in Thin Magnetic Strips - Allende-Prieto, S; Galvez-Poblete, D (American Chemical Society, 2025)
Magnetic bimerons offer a compelling alternative to skyrmions in next-generation spintronic devices. These topologically equivalent structures arise in chiral magnetic systems with in-plane magnetization driven by anisotropies or external magnetic fields. However, their use in current-driven systems is hindered by the bimeron Hall effect, which causes transverse motion and edge annihilation. Addressing these limitations, we uncover a novel mechanism for stabilizing bimeron propagation under current-driven conditions. We demonstrate that bimerons can propagate along thin ferromagnetic strips without annihilation when the easy-axis anisotropy and electric current are orthogonal. Our findings show a 6-fold velocity increase near strip edges due to boundary interactions. Furthermore, bimerons remain stable in curved geometries, allowing robust propagation in complex racetracks. This behavior also extends to bimeron chains, which propagate in parallel, forming stable and efficient configurations for information transport. These findings open new pathways toward practical and efficient bimeron-based racetrack memory technologies. © 2025 American Chemical Society.